An α-cyanostilbene type chiral fluorescent liquid crystal compound and preparation method thereof
By regulating the alkyl chain structure, an α-cyanodistyrene chiral fluorescent liquid crystal compound was prepared, and a rich liquid crystal phase state, including a double continuous cubic phase, solving the problem of difficulty in building complex structures in the prior art. Expand its potential in a variety of application areas.
Patent Information
- Application Number
- CN202411488650.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The lack of relevant reports on the prior art is difficult to construct complex dual continuous structure functional liquid crystal materials, especially in cyanodithylene derivatives, hindering its wide application in the fields of photocatalysis, photonic crystals and metamaterials.
By changing the substitution position and number of alkyl chains, the liquid crystal phase structure of the compound is regulated, and the liquid crystal phase state with equally rich chiral cubic phases are successfully obtained, including bicontinuous cubic phase phases, providing new ideas for exploring liquid crystal phase states and through specific Synthesis method to prepare α-cyanodistyrene chiral fluorescent liquid crystal compound.
It realizes liquid crystal materials with a wide temperature working range, forms a double continuous network-like three-dimensional ordered structure, and has wide application value in the fields of ion transmission, catalysis, drug transmission and energy conversion.
Smart Images

Figure CN118994289B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of liquid crystal materials, and in particular to an alpha-cyanostilbene type chiral fluorescent liquid crystal compound and a preparation method thereof. Background Art
[0002] Liquid crystals are unique self-assemblies that combine the properties of liquid and crystalline states, such as mobility and anisotropy. These properties make liquid crystals functional stimuli-responsive soft materials, mainly known for their optoelectronic response in display applications. Moreover, the incorporation of additional properties such as fluorescence into liquid crystal phases has attracted great interest, as such luminescent liquid crystals can find multiple applications in anisotropic OLEDs, simplified liquid crystal displays, chemical sensors, optical memories, or polarized organic lasers. However, it is very difficult to incorporate luminescent moieties into liquid crystal molecules while retaining liquid crystal behavior without fluorescence quenching (ACQ) by maintaining intermolecular interactions. In this regard, cyanostilbene can act as both a rod-like mesogen and a fluorescent chromophore, and cyanostilbene and its derivatives represent a good strategy to maintain both liquid crystal and luminescent properties. To date, cyanostilbene derivatives have obtained various attractive liquid crystal phases, such as nematic, smectic, and columnar phase liquid crystals, and both low-molecular and macromolecular compounds (homopolymers, copolymers, and even hydrogen-bonded supramolecular polymers) have been successfully applied.
[0003] In addition, there are mesophases (3D phases) that are periodic in all three dimensions, usually with cubic symmetry (Cub). The cubic phase is a special type of liquid crystal phase that is optically isotropic and has three-dimensional positional order. There are two basic structural forms of the cubic phase: one is the discontinuous cubic phase, which is mainly composed of spherical or nearly spherical molecules or multi-molecular aggregates stacked into a three-dimensional assembly structure; the other is the bicontinuous cubic phase, a self-assembled three-dimensional ordered interpenetrating network with cubic symmetry, which often appears in the form of an intermediate phase between the lamellar and columnar phases. Among them, the bicontinuous structure has attracted great attention in academic research and application exploration due to its attractive physical properties. For example, these structures can promote effective mass diffusion in their 3D interconnected pores, an advantage that is very desirable in electrode materials or catalysts for energy storage and conversion. The bicontinuous structure gives the material special optical properties, and the multiple light refraction and reflection in these structures can improve the efficiency of light utilization. In addition, special optical functions can be realized in bicontinuous structure materials, including photonic crystals and negative refraction. Therefore, bicontinuous structures have attracted more and more attention in the fields of photocatalysis, photonic crystals and metamaterials, and have broader application prospects. However, the construction of such complex and delicate structures is very difficult.
[0004] According to the current literature, there are no reports on these complex phase structures in cyanostilbene derivatives. This huge challenge as well as the attractive physical properties and potential applications have prompted people to develop effective methods to construct functional liquid crystal materials with bicontinuous structures. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides an α-cyanostilbene type chiral fluorescent liquid crystal compound and a preparation method thereof. The present invention regulates the liquid crystal phase structure of the compound by changing the substitution position and quantity of the alkyl chain, thereby obtaining a variety of liquid crystal phases such as smectic phase, columnar phase, and chiral cubic phase. In particular, the first discovery of chiral cubic phase liquid crystal provides a new idea for the subsequent exploration of new phases of chiral liquid crystals in cyanostilbene derivatives.
[0006] The present invention is achieved through the following technical solutions:
[0007] The first object of the present invention is to provide an α-cyanostilbene type chiral fluorescent liquid crystal compound, wherein the α-cyanostilbene type chiral fluorescent liquid crystal compound has the following structural formula: ,
[0008] Wherein, R1, R2, and R3 are one of the following:
[0009] R1 = R3 = H, R2 = OC 12 H 25 ;
[0010] R3 = H, R1 = R2 = OC 12 H 25 ;
[0011] R1 = R2 = R3 = OC 12 H 25 .
[0012] The second object of the present invention is to provide a method for preparing the α-cyanostilbene type chiral fluorescent liquid crystal compound, comprising the following steps:
[0013] (1) dissolving p-bromobenzeneacetonitrile and a catalyst tetrakis(triphenylphosphine)palladium in tetrahydrofuran, adding a sodium carbonate aqueous solution and 4-hydroxyphenylboronic acid to carry out a reflux stirring reaction, and obtaining a compound A after purification;
[0014] (2) p-Hydroxybenzaldehyde, anhydrous potassium carbonate, catalyst potassium iodide and 1-bromododecane are stirred and refluxed in acetonitrile to obtain compound B after purification;
[0015] (3) Under light-shielding conditions, the compound A obtained in step (1), the compound B obtained in step (2), and sodium hydroxide are refluxed and stirred in anhydrous methanol to obtain a compound C after purification;
[0016] (4) Cholesteryl chloride, compound C and an acid-binding agent are mixed and stirred in dichloromethane to react, and an α-cyanostilbene type chiral fluorescent liquid crystal compound is obtained after purification.
[0017] In one embodiment of the present invention, in step (1), the molar ratio of the p-bromophenylacetonitrile to the 4-hydroxyphenylboronic acid is 1:40-80.
[0018] In one embodiment of the present invention, in step (1), the reflux reaction conditions are: reflux at 75°C to 85°C for 11 h to 13 h.
[0019] In one embodiment of the present invention, in step (2), the benzaldehyde phenol is p-hydroxybenzaldehyde, 3,4-dihydroxybenzaldehyde or 3,4,5-trihydroxybenzaldehyde.
[0020] In one embodiment of the present invention, in step (2), the molar ratio of the benzaldehyde phenol to 1-bromododecane is 1:1.1-1.3;
[0021] And / or, the reflux reaction is carried out under stirring and reflux at 75° C. to 85° C. for 23 h to 24 h.
[0022] In one embodiment of the present invention, in step (3), the reflux stirring reaction conditions are: reflux stirring at 45°C~55°C for 12 h~13 h.
[0023] In one embodiment of the present invention, in step (4), the acid binding agent is triethylamine and / or diisopropylethylamine.
[0024] In one embodiment of the present invention, in step (4), the molar ratio of the cholesterol methyl chloride to the compound C is 1.2-1.5:1;
[0025] And / or, the stirring reaction condition is: stirring the reaction at room temperature for 12 h to 13 h.
[0026] The third object of the present invention is to provide the application of the α-cyanostilbene type chiral fluorescent liquid crystal compound in photocatalysis, photonic crystals or metamaterials.
[0027] The above technical solution of the present invention has the following advantages compared with the prior art:
[0028] 1. The present application provides an α-cyanostilbene type chiral fluorescent liquid crystal compound with a wide temperature operating range, which can be applied to the fields of microelectronics and functional soft matter materials.
[0029] 2. The present invention can adjust the liquid crystal phase structure of the compound by changing the substitution position and number of the alkyl chains. As the number of alkyl chains increases, the liquid crystal phase structure of the compound changes from a lamellar phase to a chiral cubic phase and finally to a columnar phase. This is also the first time that such a chiral cubic phase structure has been found in a cyanostilbene derivative, which provides a new idea for the subsequent exploration of new phases of chiral liquid crystals.
[0030] 3. The present application provides an α-cyanostilbene type chiral fluorescent liquid crystal compound, which can form two chiral network-like three-dimensional ordered structures, namely I 4132 phase and I 23 phase. This bicontinuous cubic phase has wide application value in the fields of ion transport, catalysis, drug delivery, energy conversion, etc. due to the particularity of its structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:
[0032] Figure 1 The synthetic route of compound 1-3 prepared in the examples of the present invention;
[0033] Figure 2 The TGA and DSC curves of compounds 1-3 prepared in the examples of the present invention; wherein (a) is the TGA curve of compounds 1-3; (b) is the DSC curve of compounds 1-3; 1, 2, 3 refer to compound 1, compound 2, and compound 3, respectively;
[0034] Figure 3 Polarized light microscope images of compounds 1-3 prepared in the examples of the present invention; wherein, (a) is the fingerprint texture of the TGBA phase of compound 1; (b) is the focal conic texture of compound 1 when cooled to below 190°C; (c) is the morphology of compound 2 at 132°C; (d) is the crystalline texture of compound 2 when cooled to 40°C; (e) is the fan-shaped texture of compound 3 at 88°C; (f) is the low birefringence mosaic texture of compound 3 at 66°C;
[0035] Figure 4 Small-angle X-ray scattering patterns and wide-angle X-ray scattering patterns of compounds 1-3 prepared in embodiments of the present invention; wherein (a) and (b) are small-angle X-ray scattering patterns and wide-angle X-ray scattering patterns of compound 1, respectively; (c) and (d) are small-angle X-ray scattering patterns and wide-angle X-ray scattering patterns of compound 2, respectively; (e) and (f) are small-angle X-ray scattering patterns and wide-angle X-ray scattering patterns of compound 3, respectively;
[0036] Figure 5Compounds 1-3 prepared in the examples of the present invention at different water contents ( f w ) in THF / H2O mixed solvent; (a) is the fluorescence emission diagram of compound 1 at different water contents ( f w ) in THF / H2O mixed solvent; (b) is the fluorescence emission diagram of compound 2 at different water contents ( f w ) in THF / H2O mixed solvent; (c) is the fluorescence emission diagram of compound 3 at different water contents ( f w ) in THF / H2O mixed solvent. DETAILED DESCRIPTION
[0037] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0038] The present invention provides an α-cyanostilbene type chiral fluorescent liquid crystal compound, the structural formula of which is shown below: ,
[0039] Where R1, R2, and R3 are one of the following: R1 = R3 = H, R2 = OC 12 H 25 , is compound 1; R3 = H, R1 = R2 = OC 12 H 25 , is compound 2; R1 = R2 = R3 = OC 12 H 25 , which is compound 3.
[0040] The present application also discloses a method for preparing an α-cyanostilbene type chiral fluorescent liquid crystal compound, the specific steps of which are as follows:
[0041] The first step: according to the molar ratio, 1 part of 4-bromobenzeneacetonitrile and 1 / 100 part of catalyst Pd(PPh3)4 are added to 40 to 80 parts of tetrahydrofuran, and heated and stirred at 75 to 85°C until completely dissolved to obtain a mixed solution; 3 to 6 parts of sodium carbonate are dissolved in 40 to 70 parts of distilled water to prepare a sodium carbonate aqueous solution, and then the sodium carbonate aqueous solution and 1 part of 4-hydroxyphenylboric acid are added to the mixed solution, and refluxed for 11 to 13 hours; after the reaction is completed, the tetrahydrofuran is removed under reduced pressure, and the organic layer is extracted three times with ethyl acetate and distilled water, and transferred to a clean beaker, anhydrous MgSO4 is added to dry, and the filtrate is obtained by filtering, and the solvent is removed under reduced pressure. The obtained crude product is purified by silica gel column chromatography to obtain compound A;
[0042] Step 2: According to the molar ratio, 1 part of benzaldehyde phenol, 4 to 6 parts of anhydrous potassium carbonate, 1.1 to 1.3 parts of 1-bromododecane and 0.06 parts of potassium iodide (catalyst) are added to a three-necked flask, and then 100 to 120 parts of acetonitrile are added, and stirred and refluxed at 75 to 85 ° C for 23 to 24 hours. After the reaction is completed, the reaction solution is cooled to room temperature and then filtered, and the obtained filtrate is added to distilled water for precipitation, and then filtered and washed with water until the filtrate pH = about 7. The obtained crude product is recrystallized in anhydrous ethanol and filtered to obtain compound B.
[0043] Step 3: According to the molar ratio, 1 part of the compound A, 1 part of the compound B and 1 to 2 parts of sodium hydroxide prepared above are added to 180 to 220 parts of anhydrous methanol, and refluxed and stirred at 45 to 55 ° C in the dark for 12 to 13 hours; after the reaction is completed, the reaction solution is cooled to room temperature, and dilute hydrochloric acid is added dropwise until the pH of the solution is 2 to 3 and a yellow solid appears. The yellow precipitate is collected by filtration, and the crude product is purified by silica gel column chromatography to obtain compound C;
[0044] Step 4: According to the molar ratio, 1 part of compound C and 1.2 to 1.5 parts of cholesteryl chloride are added to a round-bottom flask, and then an acid-binding agent and 200 to 300 parts of dichloromethane are added, and the mixture is stirred at room temperature for 12 to 13 hours. After the reaction is completed, the obtained reaction solution is washed with water and dried over anhydrous magnesium sulfate, and the obtained crude product is purified by silica gel column chromatography to obtain a chiral fluorescent liquid crystal material containing α-cyanodiphenylethylene units.
[0045] Furthermore, the benzaldehyde phenol in the first step is one of p-hydroxybenzaldehyde, 3,4-dihydroxybenzaldehyde or 3,4,5-trihydroxybenzaldehyde.
[0046] Furthermore, the reaction progress in the first to fourth steps was monitored by thin layer chromatography.
[0047] Preferably, the acid binding agent in the fourth step is triethylamine or diisopropylethylamine; dichloromethane needs to be dried before use to remove the moisture therein to avoid the reaction between the acyl chloride and water and reduce the yield.
[0048] Preferably, the water washing in the fourth step is to remove triethylamine, acyl chloride and soluble salts in the product; the purified elution solvent is a mixed solvent of CH2Cl2 and petroleum ether, wherein the volume ratio of CH2Cl2 to petroleum ether is 1:4 to 5, preferably 1:2.
[0049] See attached Figure 1, which is the synthesis route of the α-cyanostilbene type chiral fluorescent liquid crystal compound prepared by the present invention, namely compound 1-3; it can be seen that the difference between the three compounds is that the number of substitutions of the alkyl tail chain varies, while the subsequent synthesis steps and conditions are basically the same. Example 1
[0050] This embodiment provides a method for preparing an α-cyanostilbene type chiral fluorescent liquid crystal compound (Compound 1), and the specific steps are as follows:
[0051] Step 1, preparation of compound A: Add p-bromophenylacetonitrile (5.9 g, 30 mmol) and tetrakis(triphenylphosphine)palladium (0.35 g, 0.3 mmol) to a 250 mL three-necked flask, then add 150 mL of tetrahydrofuran, stir at 80 °C until completely dissolved, then add 30 mL of sodium carbonate (10.6 g, 100 mmol) aqueous solution and 4-hydroxyphenylboronic acid (4.3 g, 31 mmol). Reflux and stir for 12 h, and detect the reaction by thin layer chromatography until the reaction is complete (developing solvent is ethyl acetate: petroleum ether = 1: 2 v / v). After the reaction is completed, the solvent is removed by vacuum rotary evaporation, and then ethyl acetate and water are added for washing and extraction three times. Anhydrous magnesium sulfate is added to the obtained organic layer for drying, and the filtrate is obtained by suction filtration. The solvent is removed under reduced pressure, and the obtained crude product is purified by silica gel column chromatography. After drying, 5.2 g of compound A is obtained, and the yield is 83%. The prepared compound A is characterized by nuclear magnetic hydrogen spectrum, and the results are as follows:
[0052] 1 H NMR (600 MHz, DMSO- d 6), δ = 9.57 (s, 1H), 7.60 (d, J = 7.9 Hz, 2H),7.49 (d, J = 8.2 Hz, 2H), 7.37 (d, J = 7.8 Hz, 2H), 6.86-6.83 (m, 2H), 4.04(s, 2H);
[0053] Step 2, preparation of compound B1: p-hydroxybenzaldehyde (2.4 g, 20 mmol), anhydrous potassium carbonate (13.8 g, 100 mmol) and potassium iodide (0.2 g, 1.2 mmol) were added to a 250 mL three-necked flask in sequence, and then 1-bromodecane (5.5 g, 22 mmol) was weighed and added to the flask, and finally 120 mL of acetonitrile was added. Stir and reflux at 80 °C for 24 h, and the reaction was detected by thin layer chromatography until the reaction was complete (developing solvent was dichloromethane: petroleum ether = 1: 1 v / v). After the reaction was completed, the reaction solution was cooled to room temperature and then filtered, and the obtained filtrate was added to distilled water for precipitation, and then filtered and washed with water until the filtrate pH = about 7. The obtained crude product was recrystallized in anhydrous ethanol, filtered, and dried to obtain 5.3 g of compound B1, with a yield of 91%. The prepared compound B1 was characterized by nuclear magnetic hydrogen spectrum, and the results are as follows:
[0054] 1 H NMR (600 MHz, Chloroform- d ), δ = 9.88 (s, 1H), 7.85-7.80 (m, 2H), 7.01-6.97 (m, 2H), 4.03 (t, J = 6.6 Hz, 2H), 1.81 (dt, J = 14.9, 6.6 Hz, 2H),1.44 (tdd, J = 16.8, 11.8, 7.0 Hz, 2H), 1.38-1.25 (m, 16H), 0.88 (t, J = 7.0 Hz, 3H);
[0055] Step 3, preparation of compound C1: Compound A (2.0 g, 10 mmol), compound B1 (2.9 g, 10 mmol) and sodium hydroxide (0.5 g, 12.5 mmol) prepared above were added to a 250 mL three-necked flask in sequence, and then 100 mL of anhydrous methanol was added. The mixture was refluxed and stirred for 12 h at 50 °C in the dark, and the reaction was detected by thin layer chromatography until the reaction was complete (the developing solvent was petroleum ether: ethyl acetate = 2: 1 v / v). After the reaction was completed, the reaction solution was cooled to room temperature, and dilute hydrochloric acid was added dropwise until the solution pH = 2. After stirring for 1 h, a yellow solid appeared. The solid was filtered and the crude product was purified by silica gel column chromatography. After drying, 4.1 g of compound C1 was obtained, and the yield was 85%. The prepared compound C1 was characterized by nuclear magnetic hydrogen spectrum, and the results are as follows:
[0056] 1 H NMR (600 MHz, Chloroform- d ), δ = 7.89 (d, J = 8.5 Hz, 2H), 7.70(d, J = 7.9 Hz, 2H), 7.61 (d, J = 7.9 Hz, 2H), 7.52 (d, J = 7.9 Hz, 2H), 7.49(s, 1H), 6.97 (d, J = 8.4 Hz, 2H), 6.93 (d, J = 8.0 Hz, 2H), 4.02 (t, J = 6.7Hz, 2H), 1.81 (t, J = 7.5 Hz, 2H), 1.47 (t, J = 7.6 Hz, 2H), 1.37-1.26 (m,16H), 0.88 (t, J = 7.0 Hz, 3H);
[0057] Step 4, preparation of compound 1: Cholesteryl chloride (2.0 g, 4.5 mmol) and compound C1 (1.5 g, 3.2 mmol) were added to a 250 mL round-bottom flask, followed by 15 mL of triethylamine and 60 mL of dichloromethane. After stirring at room temperature for 12 h, the reaction was detected by thin layer chromatography until the reaction was complete (developing solvent was dichloromethane: petroleum ether = 1: 1 v / v). After the reaction was completed, the obtained reaction solution was washed with water and dried over anhydrous magnesium sulfate, and the obtained crude product was purified by silica gel column chromatography, and 2.6 g of compound 1 was obtained after drying, with a yield of 91%. The prepared compound 1 was characterized by nuclear magnetic hydrogen spectrum, nuclear magnetic carbon spectrum and mass spectrum, and the characterization results are shown as follows:
[0058] 1 H NMR (600 MHz, Chloroform- d ), δ = 7.90 (d, J = 8.5 Hz, 2H), 7.72(d, J = 8.1 Hz, 2H), 7.62 (dd, J = 8.3, 6.1 Hz, 4H), 7.51 (s, 1H), 7.31-7.27(m, 2H), 6.98 (d, J= 8.5 Hz, 2H), 5.43 (d, J = 5.1 Hz, 1H), 4.61 (dt, J =11.5, 6.0 Hz, 1H), 4.03 (t, J = 6.6 Hz, 2H), 2.50 (dd, J = 13.0, 8.5 Hz, 2H), 2.09-1.71 (m, 8H), 1.53-0.69 (m, 56H); 13 C NMR (151 MHz, Chloroform- d ), δ =161.06, 152.88, 150.80, 141.70, 140.45, 139.06, 137.83, 133.90, 131.19,127.99, 127.51, 126.17, 126.11, 123.19, 121.49, 118.47, 114.83, 107.78,68.18, 56.62, 56.05, 49.91, 42.25, 39.64, 39.45, 37.88, 36.77, 36.50, 36.11,35.72, 31.86, 31.77, 29.60, 29.58, 29.53, 29.51, 29.30, 29.07, 28.16, 27.95,27.59, 25.94, 24.22, 23.76, 22.76, 22.63, 22.50, 20.99, 19.23, 18.65, 14.07,11.80; MALDI-TOF-MS (C 61 H 83 NO4): The theoretical value of m / z is 893.632, the actual value is: 893.735. Example 2
[0059] This embodiment provides a method for preparing an α-cyanostilbene type chiral fluorescent liquid crystal compound (Compound 2), and the specific steps are as follows:
[0060] The first step is the preparation of compound A, as shown in Example 1.
[0061] Step 2, preparation of compound B2: 3,4-dihydroxybenzaldehyde (1.4g, 10 mmol), anhydrous potassium carbonate (13.8 g, 100 mmol) and potassium iodide (0.2 g, 1.2 mmol) were added to a 250 mL three-necked flask in sequence, and then 1-bromodecane (5.5 g, 22 mmol) was weighed and added to the flask, and finally 120 mL of acetonitrile was added. Stir and reflux at 80 °C for 24 hours, and the reaction was detected by thin layer chromatography until the reaction was complete (developing solvent was dichloromethane: petroleum ether = 1: 1 v / v). After the reaction was completed, the reaction solution was cooled to room temperature and then filtered, and the obtained filtrate was added to distilled water for precipitation, and then filtered and washed with water until the filtrate pH = about 7. The obtained crude product was recrystallized in anhydrous ethanol, filtered, and dried to obtain 4.2 g of compound B2, with a yield of 89%. The prepared compound B2 was characterized by nuclear magnetic hydrogen spectrum, and the results are as follows:
[0062] 1 H NMR (600 MHz, Chloroform- d ), δ = 9.83 (s, 1H), 7.41 (dd, J = 8.1,1.9 Hz, 1H), 7.39 (d, J = 1.8 Hz, 1H), 6.95 (d, J = 8.2 Hz, 1H), 4.06 (dt, J = 17.0, 6.7 Hz, 4H), 1.88-1.81 (m, 4H), 1.47 (dt, J = 7.8, 4.4 Hz, 4H), 1.38-1.25 (m, 32H), 0.88 (t, J = 7.0 Hz, 6H);
[0063] Step 3, preparation of compound C2: Compound A (0.9 g, 4.2 mmol), compound B2 (2.0 g, 4.2 mmol) and sodium hydroxide (0.5 g, 12.5 mmol) prepared above were added to a 100 mL three-necked flask in sequence, and then 50 mL of anhydrous methanol was added. The mixture was refluxed and stirred for 12 h at 50 °C in the dark, and the reaction was detected by thin layer chromatography until the reaction was complete (developing agent was petroleum ether: dichloromethane = 1: 2 v / v). After the reaction was completed, the reaction solution was cooled to room temperature, and dilute hydrochloric acid was added dropwise until the solution pH = 2. After stirring for 1 h, a yellow solid appeared. The solid was filtered and the crude product was purified by silica gel column chromatography. After drying, 2.35 g of compound C2 was obtained, and the yield was 84%. The prepared compound C2 was characterized by nuclear magnetic hydrogen spectrum, and the results were as follows:
[0064] 1 H NMR (600 MHz, Chloroform- d ), δ = 7.70 (d, J = 8.2 Hz, 2H), 7.67(d, J = 2.1 Hz, 1H), 7.60 (d, J = 8.2 Hz, 2H), 7.54-7.50 (m, 2H), 7.47 (s,1H), 7.37 (dd, J = 8.4, 2.1 Hz, 1H), 6.94-6.92 (m, 2H), 6.91 (s, 1H), 4.08(dt, J = 18.9, 6.6 Hz, 4H), 1.85 (tt, J = 6.6, 3.3 Hz, 4H), 1.49 (q, J = 7.5,7.0 Hz, 4H), 1.40-1.23 (m, 32H), 0.88 (td, J = 7.0, 2.6 Hz, 6H);
[0065] Step 4, preparation of compound 2: Cholesteryl chloride (1.7 g, 3.8 mmol) and compound C2 (2.0 g, 3 mmol) were added to a 250 mL round-bottom flask, followed by 15 mL of triethylamine and 60 mL of dichloromethane. After stirring at room temperature for 12 h, the reaction was detected by thin layer chromatography until the reaction was complete (developing solvent was dichloromethane: petroleum ether = 1: 1 v / v). After the reaction was completed, the obtained reaction solution was washed with water and dried over anhydrous magnesium sulfate, and the obtained crude product was purified by silica gel column chromatography, and 2.9 g of compound 2 was obtained after drying, with a yield of 90%. The prepared compound 2 was characterized by nuclear magnetic hydrogen spectrum, nuclear magnetic carbon spectrum and mass spectrometry, and the characterization results are shown as follows:
[0066] 1 H NMR (600 MHz, Chloroform- d ), δ = 7.72 (d, J = 8.2 Hz, 2H), 7.68(d, J = 2.1 Hz, 1H), 7.62 (dd, J = 8.2, 5.7 Hz, 4H), 7.48 (s, 1H), 7.37 (dd, J = 8.5, 2.1 Hz, 1H), 7.28 (d, J = 8.4 Hz, 2H), 6.92 (d, J = 8.4 Hz, 1H),5.45-5.41 (m, 1H), 4.61 (tt, J = 10.9, 5.0 Hz, 1H), 4.08 (dt, J = 18.4, 6.6Hz, 4H), 2.56-2.45 (m, 2H), 2.07-1.72 (m, 10H), 1.53-0.68 (m, 77H); 13 C NMR (151 MHz, Chloroform- d), δ = 153.30, 151.86, 151.26, 149.43, 142.45, 140.88,139.51, 138.26, 134.40, 128.41, 127.93, 126.93, 126.55, 124.66, 123.61,121.91, 118.97, 113.57, 113.18, 69.67, 69.47, 57.06, 56.51, 50.37, 42.70,40.09, 39.89, 38.32, 37.21, 36.94, 36.55, 36.16, 32.29, 32.22, 30.07, 30.03,29.99, 29.80, 29.76, 29.74, 29.55, 29.48, 28.59, 28.38, 28.03, 26.42, 26.36,24.65, 24.20, 23.18, 23.06, 22.92, 21.43, 19.66, 19.09, 14.48, 12.23; MALDI-TOF-MS (C 73 H 107 NO5): m / z theoretical value is 1077.815, actual value is: 1077.776. Example 3
[0067] This embodiment provides a method for preparing an α-cyanostilbene type chiral fluorescent liquid crystal compound (Compound 3), and the specific steps are as follows:
[0068] The first step is the preparation of compound A, as shown in Example 1.
[0069] Step 2, preparation of compound B3: 3,4,5-trihydroxybenzaldehyde (1.5 g, 10 mmol), anhydrous potassium carbonate (16.6 g, 120 mmol) and potassium iodide (0.3 g, 1.8 mmol) were added to a 250 mL three-necked flask in sequence, and then 1-bromodecane (8.2 g, 33 mmol) was weighed and added to the flask, and finally 120 mL of acetonitrile was added. Stir and reflux at 80 °C for 24 h, and the reaction was detected by thin layer chromatography until the reaction was complete (developing solvent was dichloromethane: petroleum ether = 1: 1 v / v). After the reaction was completed, the reaction solution was cooled to room temperature and then filtered, and the filtrate was added to distilled water for precipitation, and then filtered and washed with water until the filtrate pH = about 7. The crude product was recrystallized in anhydrous ethanol, filtered, and dried to obtain 5.6 g of compound B3 with a yield of 85%. The prepared compound B3 was characterized by H NMR spectrum, and the results were as follows:
[0070] 1 H NMR (300 MHz, Chloroform- d ), δ = 9.83 (s, 1H), 7.08 (s, 2H), 4.03(t, J = 6.7 Hz, 6H), 1.89-1.70 (m, 6H), 1.46 (d, J = 7.8 Hz, 6H), 1.28 (d, J = 10.3 Hz, 48H), 0.93-0.83 (m, 9H);
[0071] Step 3, preparation of compound C3: Compound A (0.4 g, 2 mmol), compound B3 (1.3 g, 2 mmol) and sodium hydroxide (0.5 g, 12.5 mmol) prepared above were added to a 100 mL three-necked flask in sequence, and then 50 mL of anhydrous methanol was added. The mixture was refluxed and stirred for 12 h at 50 °C in the dark, and the reaction was detected by thin layer chromatography until the reaction was complete (developing agent was petroleum ether: dichloromethane = 1: 2 v / v). After the reaction was completed, the reaction solution was cooled to room temperature, and dilute hydrochloric acid was added dropwise until the solution pH = 2. After stirring for 1 h, a yellow solid appeared. The solid was filtered and the crude product was purified by silica gel column chromatography. After drying, 1.44 g of compound C3 was obtained, and the yield was 85%. The prepared compound C3 was characterized by nuclear magnetic hydrogen spectrum, and the results were as follows:
[0072] 1 H NMR (300 MHz, Chloroform- d ), δ = 7.70 (d, J = 8.4 Hz, 2H), 7.61(d, J = 8.3 Hz, 2H), 7.55-7.49 (m, 2H), 7.44 (s, 1H), 7.17 (s, 2H), 6.97-6.90(m, 2H), 4.05 (td, J = 6.5, 2.6 Hz, 6H), 1.80 (dt, J = 21.2, 7.4 Hz, 6H),1.49 (t, J = 7.6 Hz, 6H), 1.29 (d, J = 12.4 Hz, 48H), 0.88 (t, J = 6.5 Hz,9H);
[0073] Step 4, preparation of compound 3: Cholesteryl chloride (0.6 g, 1.3 mmol) and compound C3 (0.85 g, 1 mmol) were added to a 250 mL round-bottom flask, followed by 15 mL of triethylamine and 60 mL of dichloromethane. After stirring at room temperature for 12 h, the reaction was detected by thin layer chromatography until the reaction was complete (developing solvent was dichloromethane: petroleum ether = 1: 1 v / v). After the reaction was completed, the obtained reaction solution was washed with water and dried over anhydrous magnesium sulfate, and the obtained crude product was purified by silica gel column chromatography, and 1.16 g of compound 3 was obtained after drying, with a yield of 92%. The prepared compound 3 was characterized by nuclear magnetic hydrogen spectrum, nuclear magnetic carbon spectrum and mass spectrum, and the characterization results are shown as follows:
[0074] 1 H NMR (600 MHz, Chloroform- d ), δ = 7.72 (d, J = 8.1 Hz, 2H), 7.63(t, J = 8.3 Hz, 4H), 7.46 (s, 1H), 7.29 (d, J = 8.3 Hz, 2H), 7.17 (s, 2H), 5.43 (d, J = 5.0 Hz, 1H), 4.61 (tt, J = 10.9, 5.0 Hz, 1H), 4.05 (q, J = 6.4Hz, 6H), 2.51 (tt, J = 14.7, 8.7 Hz, 2H), 2.08-1.73 (m, 12H), 1.52-0.68 (m, 98H); 13 C NMR (151 MHz, Chloroform- d), δ = 153.57, 142.65, 128.43, 127.96,126.68, 123.62, 121.93, 108.39, 74.01, 69.62, 57.06, 56.51, 50.37, 40.09,39.89, 38.32, 37.21, 36.55, 36.16, 32.30, 32.22, 30.72, 30.12, 30.07, 30.03,30.01, 29.96, 29.79, 29.76, 29.73, 29.71, 28.59, 28.38, 28.03, 26.49, 26.45,24.65, 24.20, 23.18, 23.06, 22.92, 21.43, 19.66, 19.08, 14.48, 12.23; MALDI-TOF-MS (C 85 H 131 NO6): m / z theoretical value is 1261.998, actual value is: 1261.977.
[0075] Test Example 1
[0076] Compounds 1-3 prepared in Example were subjected to TGA and DSC tests: 5 mg of sample was taken in a crucible respectively, and heated from room temperature to 700 ºC at a rate of 10 ºC / min under N2 atmosphere to obtain TGA curves. It was found that the temperature at which the three compounds lost 5% of their weight was more than 265 ℃; below the decomposition temperature, another 5 mg of sample was taken in a crucible, and heated from room temperature to above the isotropic temperature at a rate of 10 ºC / min under N2 atmosphere, kept warm for 1 min, then cooled to -20 ºC, kept warm for 1 min, and heated from -20 ºC to above the isotropic temperature again, and the DSC curves of the first cooling and second heating processes were obtained. The results are shown in the attached Figure 2 From the test results, compound 1 only showed one strong peak during the heating and cooling process. The exothermic peak at 89.6 °C during the cooling process corresponded to the crystallization peak of the compound. The exothermic peaks of compound 2 at 178.1 °C and compound 3 at 89.2 °C corresponded to the transition of the compound from the isotropic state to the liquid crystal state, indicating that the increase in the number of alkyl tail chains of the compound will lead to a decrease in the temperature at which the sample enters the isotropic state.
[0077] Test Example 2
[0078] 1 mg of each compound 1-3 prepared in the example was taken between two cover glasses and placed on a heating table for POM test. After the temperature was raised to above the isotropic temperature, pictures were taken during the slow cooling process. See attached Figure 3 POM observation found that compound 1 began to melt and enter the liquid crystal state at 127 °C. When the temperature continued to rise, it was found that its extinction temperature was very high and close to the decomposition temperature. However, it would enter a state similar to the isotropic phase above 200 °C, except that there was birefringence at the edge of the bubble. When the temperature was lowered in this state, the following would appear: Figure 3 The fingerprint texture of the TGBA phase shown in (a) appears when the temperature is lowered to below 190 °C. Figure 3 As shown in (b), the sample started to crystallize when the temperature was further lowered to 85 °C. When the temperature of compound 2 was raised from room temperature to 102 °C, the birefringence suddenly disappeared. At this time, the sample was molten but the viscosity was very high. When the temperature was further raised to about 200 °C, the sample became a flowing liquid and entered an isotropic state, which was consistent with the change of the DSC curve. No birefringence was observed during the cooling process until the crystal texture appeared when the temperature was lowered to 40 °C, as shown in Figure 3 Compound 3 enters isotropic state at about 100 °C, and begins to show fan-shaped texture at about 89 °C during the cooling process, and then begins to grow low birefringence mosaic texture at about 85 °C, as shown in (c) and (d). Figure 3 As shown in (e) and (f), all of them have this texture at the end and are kept at room temperature. Compounds 1 and 3 both have typical liquid crystal textures, indicating that they both have liquid crystal properties, while compound 2 may have formed a special cubic phase structure.
[0079] Test Example 3
[0080] 2 mg to 3 mg of the compounds 1 to 3 prepared in the examples were respectively placed in an XRD capillary tube for small angle X-ray scattering test. The results are shown in the attached Figure 4 .like Figure 4 As shown in (a) and (b), compound 1 has a sharp diffraction peak in the wide-angle region when the temperature is below 110 °C, indicating that the compound is crystalline; when heated to 140 °C, the original sharp diffraction peak in the wide-angle region disappears and a broad peak appears. At this time, the sample enters the liquid crystal state. The two diffraction peaks appearing in the small-angle region are q The values are 1.61 nm -1 , 3.19 nm -1 , which correspond to the (001) and (002) diffraction planes of the layered structure, respectively, which means that compound 1 forms a layered stacking within this temperature range, and the interlayer spacing is d The peak of the diffraction peak of the sample is 3.90 nm. When the sample is heated to a higher temperature, there is only one high and sharp diffraction peak. Combined with the POM results, the sample enters the TGBA phase. Compound 2 is crystalline at room temperature. When the temperature is raised to 120 °C, compound 2 shows 12 diffraction peaks in the small angle region. q The values are 0.92 nm -1 , 1.60 nm -1, 1.85 nm -1 , 2.09 nm -1 , 2.27 nm -1 , 2.44 nm -1 , 2.62 nm -1 , 2.78 nm -1 , 2.93 nm -1 , 3.07 nm -1 , 3.20 nm -1 and 3.34 nm -1 , it was found through calculation that these diffraction peaks correspond to I The diffraction planes of the 4132 structure are (110), (211), (220), (310), (222), (321), (400), (330), (420), (332), (422), and (510). The structural parameter a = 9.5 nm, which means that the compound enters the cubic phase at this temperature. At this time, the sample viscosity is very high and no birefringence is observed. When the temperature is further increased, the phase structure of the compound remains unchanged from 150 ℃ to 185 ℃. Taking 185 ℃ as an example, multiple diffraction peaks are shown in the small angle region. q The values are 0.60 nm -1 , 0.87 nm -1 , 1.05 nm -1 , 1.23 nm -1 , 1.35 nm -1 , 1.48 nm -1 , 1.59 nm -1 , 1.71 nm -1 , 1.80 nm -1 , 1.91 nm -1 , 2.09 nm -1 , 2.18 nm -1 , 2.34 nm -1 , 2.62 nm -1 and 3.13 nm -1 , it was found through calculation that these diffraction peaks correspond to I The diffraction surfaces of (110), (200), (211), (220), (310), (222), (321), (400), (411), (420), (422), (431), (521), (532), (633) of the 23 structure, the structural parameter a = 14.8 nm, compound 2 is self-assembled from I 4132 entered I 23 phase; when heated to 220 °C, it enters the isotropic state, such as Figure 4As shown in (c) and (d) in the figure. Compound 3 is also crystalline at room temperature. When the temperature rises to about 120 °C, the compound enters isotropic state. During the cooling process, the compound appears at 90 °C. q The values are 1.73 nm -1 , 3.02 nm -1 , 3.48 nm -1 The three diffraction peaks of q The ratio is 1:3 1 / 2 : 2, indicating that the compound enters Col h Phase, according to the formula a= 4π / 3 1 / 2 q , the structural parameters can be calculated a = 4.2 nm, Figure 4 As shown in (e) and (f) in the figure; when the temperature continues to drop to 70 ℃, an unknown phase is entered, corresponding to a mosaic texture. Due to the many peaks on the SAXS curve, the situation is complicated, and there are problems such as weak signal intensity and insufficient resolution, the phase state cannot be determined at present. In the future, in-depth research will be continued through synchrotron radiation and other technologies to determine the phase structure.
[0081] Test Example 4
[0082] The compounds 1-3 prepared in the examples were studied at different water contents ( f w ) in a THF / H2O mixed solvent with a concentration of 1 × 10 -5 mol / L, see the attached Figure 5 Compound 1 f w When the f w < 50%) has almost no fluorescence emission intensity. f w When the water content of compound 1 increases to 50%, the fluorescence intensity of compound 1 increases significantly with the increase of water content, showing a significant AIE effect. f w It increases with the continuous increase of , and also shows obvious AIE effect.
[0083] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. An α-cyanostilbene type chiral fluorescent liquid crystal compound, characterized in that: The α-cyanostilbene type chiral fluorescent liquid crystal compound has the following structural formula: , Wherein, R1, R2, and R3 are one of the following: R1 = R3 = H,R2 = OC 12 H 25 ; R3 = H,R1 = R2 = OC 12 H 25 ; R1 = R2 = R3 = OC 12 H 25 。 2. The method for preparing an α-cyanostilbene type chiral fluorescent liquid crystal compound according to claim 1, characterized in that: The following steps are involved: (1) dissolving p-bromobenzeneacetonitrile and a catalyst tetrakis(triphenylphosphine)palladium in tetrahydrofuran, adding a sodium carbonate aqueous solution and 4-hydroxyphenylboronic acid to carry out reflux stirring reaction, and obtaining a compound A after purification; the structural formula of the compound A is: ; (2) Benzaldehyde phenol, anhydrous potassium carbonate, catalyst potassium iodide and 1-bromododecane are stirred and refluxed in acetonitrile to obtain compound B after purification; the structural formula of compound B is: ; Wherein, R1, R2, R3 are one of the following: R1 = R3 = H, R2 = OC 12 H 25 ; R3 = H, R1 = R2 = OC 12 H 25 ; R1 = R2 = R3 = OC 12 H 25 ; (3) Under light-shielding conditions, the compound A obtained in step (1), the compound B obtained in step (2) and sodium hydroxide are refluxed and stirred in anhydrous methanol to react, and compound C is obtained after purification; the structural formula of the compound C is: ; Where R1, R2, and R3 are one of the following: R1 = R3 = H, R2 = OC 12 H 25 ; R3 = H, R1 = R2 = OC 12 H 25 ; R1 = R2 = R3 = OC 12 H 25 ; (4) mixing cholesteryl chloride, compound C and an acid-binding agent in dichloromethane and stirring them for reaction, and obtaining an α-cyanostilbene type chiral fluorescent liquid crystal compound after purification; In step (2), the benzaldehyde phenol is p-hydroxybenzaldehyde, 3,4-dihydroxybenzaldehyde or 3,4,5-trihydroxybenzaldehyde.
3. The preparation method according to claim 2, characterized in that: In step (1), the molar ratio of the p-bromophenylacetonitrile to the 4-hydroxyphenylboronic acid is 1:40-80.
4. The preparation method according to claim 2, characterized in that: In step (1), the reflux reaction conditions are: reflux at 75°C to 85°C for 11 h to 13 h.
5. The preparation method according to claim 2, characterized in that: In step (2), the molar ratio of the benzaldehyde phenol to 1-bromododecane is 1:1.1-1.3; And / or, the reflux reaction is carried out under stirring and reflux at 75° C. to 85° C. for 23 h to 24 h.
6. The preparation method according to claim 2, characterized in that: In step (3), the reflux stirring reaction conditions are: reflux stirring at 45°C~55°C for 12 h~13 h.
7. The preparation method according to claim 2, characterized in that: In step (4), the acid binding agent is triethylamine and / or diisopropylethylamine.
8. The preparation method according to claim 2, characterized in that: In step (4), the molar ratio of the cholesterol methyl chloride to the compound C is 1.2-1.5:1; And / or, the stirring reaction condition is: stirring the reaction at room temperature for 12 h to 13 h.
